Bahasa Humor dalam Playlist Cerita Cintaku 2022 pada Kanal YouTube Raditya Dika: Tinjauan Pragmatik - Dewi, Muthia Triana; Aslinda, Aslinda; Darmawan, Alex (Universitas Andalas, 2024)
Language is always used in everyday communication. During the communication process, cooperation between the speaker and the interlocutor is necessary. The principle of cooperation is one of the studies in pragmatics. Many violations of the cooperative principle can create humor, but not only violations; adherence can also create humor, and this can be seen in the Playlist Cerita Cintaku 2022 on the YouTube channel Raditya Dika. This research aims to explain the maxims of the cooperative principle that are adhered to and violated in the Playlist Cerita Cintaku 2022 on the YouTube channel Raditya Dika and to explain the techniques of creating a humorous language based on the language categories found in the Playlist Cerita Cintaku 2022 on the YouTube channel Raditya Dika. There are three stages of research, namely the data provision stage, data analysis stage, and presentation of data analysis results stage. In the data provision stage, the method and techniques used are the observation method with basic tapping technique and advanced technique of Free Involvement Conversation Observation (FIC) and note-taking. In the data analysis stage, the method and techniques used are the pragmatic equivalence method with basic Determining Element Selection (DES) technique and advanced techniques of Comparing Similarities (CS) and Comparing Differences (CD). In the presentation of data analysis results stage, an informal presentation method is used. From the data analysis results, there are cooperative principle maxims that are adhered to, namely the maxim of quantity, the maxim of quality, and the maxim of relevance. The violations of the cooperative principle maxims identified are the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. Then, there are techniques for creating humor based on language categories, namely: bombast, definition, facetiousness, infantilism, over-literalness, pun, wordplay, repartee, ridicule, sarcasm, and satire. From these techniques, it can be seen that the violation of the maxims of the cooperative principle is the most prevalent in creating humor.